2023
DOI: 10.1017/flw.2023.15
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and financial wellbeing: Evidence from Peru and Uruguay

Catalina Estrada-Mejia,
Diana Mejía,
Paula Córdoba

Abstract: In this paper, we provide an analysis of financial literacy in Peru and Uruguay. We find that the knowledge of simple concepts at the basis of financial decision-making is low in both countries. Not only is financial illiteracy widespread, but it is particularly acute among women, rural populations, the less educated, low-income people, the self-employed, the not employed, younger people (in the case of Peru), and older people (in the case of Uruguay). We also find that financial literacy is linked to measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…This is supported by the study of Brau et al [35], which found that students with financial learning opportunities score higher on financial literacy tests and surveys. In contrast, Estrada-Mejia et al [36], found that individuals residing in rural areas, with low income, women, and those with lower levels of education, exhibit low financial literacy levels in both Peru and Uruguay.…”
Section: Permission From Organization/locationmentioning
confidence: 91%
“…This is supported by the study of Brau et al [35], which found that students with financial learning opportunities score higher on financial literacy tests and surveys. In contrast, Estrada-Mejia et al [36], found that individuals residing in rural areas, with low income, women, and those with lower levels of education, exhibit low financial literacy levels in both Peru and Uruguay.…”
Section: Permission From Organization/locationmentioning
confidence: 91%